Groundwater Modelling Using GIS Techniques: A Case Study Bagh River Watershed Area of Gondia District - Hanuwate, Sandeepkumar Chandulal; Kumar, G. Shravan (International Journal of Membrane Science and Technology, 2023)
Geographical information systems (GIS) are the most important mapping and modeling tool for groundwater level resources in the present day. There was a challenge to define the groundwater level of A case study Bagh River watershed area pre-monsoon and post-monsoon analysis of Birsola Village, Gondia District, Maharashtra, India, is confronted with the issue of groundwater availability within a few years. To evaluate the suitability of groundwater levels using GIS interpolation model techniques, one must determine the groundwater level's suitability. Geospatial techniques working for Geographical information systems (GIS) are increasingly utilized in water resources management, hydrology, and groundwater level monitoring. This is the greatest benefit of utilizing GIS interpolation techniques. This method of study of groundwater level monitoring to generate data on water level potential position conditions in the area under study is crucial for successful analysis, prediction, and validation. The result is determined by analysis of physicochemical parameters with statistical significance and using the GIS technique for groundwater modeling.